Cash Processing Administration System In The Indonesian Red Cross Blood Transfusion Unit, Semarang City - Okky Dwianto Wahyu Nugrohojati; Eko Siswanto; Bagus Sudirman (Lembaga Pengembangan Kinerja Dosen, 2022)
The cash processing administration system in a company plays a very important role. One of the problems that often arises in a cash processing administration system is the inaccurate calculation results of cash administration reports. This can result in inaccurate calculations of a company's profits and losses. Besides that, the use of company funds for something is not necessary, because every income and expenditure of company funds can be seen clearly and can be checked at any time. In short, companies will be able to quickly and easily find out the income and expenditure of funds. Information technology which is developing rapidly at this time provides very helpful benefits for the development of a company's information system, especially with the use of computer-based information technology, because by using computer technology in an information system you will be able to process data more quickly with lower error rates. minimal and saves time. The procedures that will be processed consist of the administration section and the finance section. If there is an income or expenditure of money or funds, the data can simultaneously be entered into the computer and will automatically influence or add to the existing data in the company. In this way, the condition of the money or funds in the company can be known with certainty and accuracy.